GERMAN-ISRAEL RELATIONS IN THE CONTEXT OF THE MIDDLE EAST PEACE PROCESS PROBLEMS (2005 – 2014) - M. V. Streletz (Вестник Кемеровского государственного университета, 2014)
The subject of the article is that aspect of the Israeli Merkel government's foreign policy vector in Germany, which is associated with the search for a peaceful settlement in the Middle East. Based on comparative-historical method, the author for the first time in post-Soviet historiography has attempted to identify general and specific in approaches Berlin and Tel-Aviv in the subject matter in the same period. Appeal to this purpose of the research process helps to understand the possibilities and limits of the German-Israel cooperation on the subject of the Middle East peace settlement. The main result of this process was a comprehensive analysis of the discussions for a peaceful settlement in this region on the GermanIsrael negotiations at the highest levels from 2005 – 2014. The author leads to the following conclusions: 1) German Middle East policy is in a tense relationship between the historical responsibility towards Israel and trustworthy German-Israel settling solutions; 2) during Merkel reign she only partially has managed to align these goals. This article could be interesting for scholars of international affairs, as well as diplomats who are involved on the German-Israel relationships.